2012
DOI: 10.1080/08927014.2012.749398
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids of plant origin inhibit morphogenesis, adhesion, and biofilm formation byCandida albicans

Abstract: Biofilm-related infections caused by Candida albicans and associated drug resistant micro-organisms are serious problems for immunocompromised populations. Molecules which can prevent or remove biofilms are needed. Twenty-eight terpenoids of plant origin were analysed for their activity against growth, virulence attributes, and biofilms of C. albicans. Eighteen molecules exhibited minimum inhibitory concentrations of <2 mg ml(-1) for planktonic growth. Selected molecules inhibited yeast to hyphal dimorphism at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 31 publications
6
97
2
Order By: Relevance
“…Values in the control and treatment groups were compared using Student's t-test. A value of p < 0.05 was considered statistically significant [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Values in the control and treatment groups were compared using Student's t-test. A value of p < 0.05 was considered statistically significant [10].…”
Section: Discussionmentioning
confidence: 99%
“…The adherence of cells were observed in each well by relative metabolic activity (RMA) using the XTT-assay [10].…”
Section: Adhesion Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have reported the discovery of nonazole compounds (11,13), immunosuppressive drugs (14), tunicamycin (15), and farnesol (16), among others. Additionally, numerous studies have evaluated repurposed agents as part of antifungal lock solutions against C. albicans biofilms, including ethanol (17,18), heparin (9), doxycycline (19), chitosan (20), EDTA (21), and tigecycline (8).…”
mentioning
confidence: 99%